Remote sensing, GIS, the geospatial technologies, and Unmanned Airborne Vehicles at Aberdeen University. - Green, David R. (Scottish Geographical Journal)
Aberdeen University has a long history of using aerial photography, photogrammetry, cartography, remote sensing and surveying in Geography teaching and research. The development of an MSc in Environmental Remote Sensing (ERS) in 1987 offered students a new opportunity to specialise further in this rapidly evolving area of technology. The programme has continued to thrive and the MSc in GIS celebrated its 30th Anniversary in 2017. Recently the degree has included courses on current applications of GIS and web-GIS. The introduction of UAV (Unmanned Aerial Vehicle) remote sensing broadened the appeal and competitiveness of the degree, ensuring students have access to cutting edge remote sensing technology. Alongside PhD studies, applied academic research in the Aberdeen Institute for Coastal Science and Management (AICSM), and the Unmanned Airborne Vehicle (UAV)/Unmanned Airborne System (UAS) Centre for Environmental Monitoring and Mapping (UCEMM), make widespread use of GIS and remote sensing. As the geospatial technologies continue to evolve and are integrated with drones the role of education, training and research utilising these technologies will become integral to the Geography degree. Geospatial technologies have and will continue to provide valuable tools and techniques for graduates.